(untitled) (GESTIÓN Y TENDENCIAS, 2024)
The business model is a term widely used in entrepreneurship, innovation, and business strategy, although its definition and components are often perceived as blurred. This article focuses on three key areas: definitions, the "business model canvas", and its application. A business model serves as a detailed map that answers crucial questions about why customers choose a company and how it generates revenue. The Business Model Canvas is a widely recognized tool for understanding and designing business models. It comprises nine blocks addressing aspects such as customer segments, value proposition, channels, customer relationships, key resources, key activities, key partners, cost structure, and revenue streams. The use of the canvas is illustrated through the case of Marvel Studios, showing how this approach helps visualize the structure of the business model.